Prospects of Dwarf Coconut (Cocos nucifera L. var. genjah) as a Cultivar for Coconut Sugar Production in East Lampung - Lukman Efendi; Analianasari Analianasari; Surfiana Surfiana (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Coconut sugar is emerging as a promising natural sweetener to reduce Indonesia’s dependency on imported refined sugar. Among various coconut cultivars, Cocos nucifera L. var. genjah (dwarf coconut) offers advantages for sap production due to its short trunk, early maturity, and high sugar content. This study aimed to examine the prospects of dwarf coconut as a productive cultivar for coconut sugar development in East Lampung Regency, based on field-level adoption indicators. A total of 41 respondents were selected using Slovin’s formula. Primary data were collected through structured interviews and analyzed using descriptive statistics, T-tests, and multiple linear regression with SPSS version 27. The findings show that factors such as landholding size, formal education exposure, and income levels significantly (P < 0.05) influence the practical use of dwarf coconut for coconut sugar production. These results highlight the potential of dwarf coconut as a strategic cultivar to support local coconut sugar initiatives in Indonesia.